Strategi Public Relations Solo Paragon Lifestyle Mall Dalam Meningkatkan Corporate Image Melalui Tema "Shopping, Dining And Entertainment" - Maulanna, Dhiqy Arendra (2016)
The image of the company is very necessary because the presence of a positive image will determine the success and sustainability of a company. The development of shopping centers in the city of Solo is increasing, it makes a lot of mall doing a variety of ways in order to compete with other competitors. This is a concern especially Public Relations Solo Paragon Lifestyle Mall to maintain and enhance positive corporate image through the theme of shopping, dining and entertainment. This study aimed to find out Strategic Public Relations Solo Paragon Lifestyle Mall in improving corporate image through the theme "Shopping, Dining and Entertainment. This research uses descriptive qualitative research methods. The object of this study conducted in Solo Paragon Lifestyle Mall. Sampling is done by using purposive sampling technique. Sources of data used in the study informants are Public Relations, Marketing Communications and visitors Solo Paragon Lifestyle Mall. The technique of collecting data by conducting interviews, observation, and documentation. Analysis using Interactive Models of Analysis. While the technical validity of the data using the method of triangulation data. The conclusion that can be drawn from this study, Public Relations Solo Paragon Lifestyle Mall here in improving corporate image by conducting promotional programs by providing a variety of information on all matters relating to the mall and always give the best to the visitors in terms of shopping, dining and entertainment. For in improving the image of the company in order to remain positive and well regarded in the eyes of the public is something very important for the sustainability of a company itself.